Applying the ecosystem services - EBM framework to sustainably manage Qatar's coral reefs and seagrass beds - Lucia M. Fanning (16928394) (2021)
Given the current natural and anthropogenic threats facing Qatar’s marine environment and the consequential expected decline in ecosystem services, this paper examines the potential application of the Ecosystem ServicesEBM framework developed by Granek et al. (2010) to sustainably manage Qatar’s coral reef and seagrass bed ecosystems. Using interviews with stakeholders and field-collected data from sixteen coral reef sites and 6 seagrass meadows as well as secondary data, the paper presents new knowledge regarding the status of these ecosystems and the benefits they provide that are most valued by stakeholders. The research identifies existing and missing ecological and socio-economic data, as well as the processes and management strategies required to implement the five-step framework within a Qatari context. Key goals for implementing EBM identified by stakeholders include: adoption of scientific planning and valuation of marine environment, contextualizing and drafting legislation, regulations and policies in support of EBM; monitoring and enforcement of laws; and, promotion of public awareness and engagement. The article concludes with recommendations for filling remaining data gaps and highlights opportunities available to Qatar to become a leader in implementing EBM. These include maximizing the increasing role that stakeholders can play in mitigating further decline of the country’s coastal ecosystems and leveraging mega events planned in Qatar, such as FIFA World Cup 2022. Other Information Published in: Ocean & Coastal Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ocecoaman.2021.105566